The Impact of Online Gambling on Marital Relationships and Divorce Rates: A Literature Review - Pirdaus, Dede Irman; Kalfin, Kalfin; Salih, Yasir (Research Collaboration Community (RCC), 2024)
The prevalence of online gambling has soared in recent years, posing a significant threat to marital relationships and divorce rates. This research examines the impact of online gambling on marital relationships and levels of peace through comprehensive literature insights. This study analyzes the development of online gambling, the factors that encourage participation, the psychological impact, and its influence on marital dynamics. Findings show that online gambling can significantly damage marital relationships, cause financial conflict, reduce the quality of communication, and increase the risk of divorce. Statistical data from Indonesia shows an increase in gambling-related divorce cases in the last five years, with a peak in 2023. This research highlights the need for multi-faceted interventions, including stricter regulations, public awareness campaigns and support services for affected families to reduce Negative effects of online gambling on marriage.